2017
DOI: 10.1007/978-3-319-58741-7_26
|View full text |Cite
|
Sign up to set email alerts
|

Surjective H-Colouring: New Hardness Results

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Surj H-Colouring H-Colouring Figure 1: Relations between Surjective H-Colouring and its variants (from [15]). An arrow from one problem to another indicates that the latter problem is polynomial-time solvable for a graph H whenever the former is polynomial-time solvable for H. Reverse arrows do not hold for the leftmost and rightmost arrows, as witnessed by the reflexive 4-vertex cycle for the rightmost arrow and by any reflexive tree that is not a reflexive interval graph for the leftmost arrow (Feder, Hell and Huang [11] showed that the only reflexive bi-arc graphs are reflexive interval graphs).…”
Section: H-retraction H-compactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surj H-Colouring H-Colouring Figure 1: Relations between Surjective H-Colouring and its variants (from [15]). An arrow from one problem to another indicates that the latter problem is polynomial-time solvable for a graph H whenever the former is polynomial-time solvable for H. Reverse arrows do not hold for the leftmost and rightmost arrows, as witnessed by the reflexive 4-vertex cycle for the rightmost arrow and by any reflexive tree that is not a reflexive interval graph for the leftmost arrow (Feder, Hell and Huang [11] showed that the only reflexive bi-arc graphs are reflexive interval graphs).…”
Section: H-retraction H-compactionmentioning
confidence: 99%
“…This paper concerns the computational complexity of the surjective homomorphism problem, also known in the literature as Surjective H-Colouring [15,16] and H-Vertex-Compaction [30]. This problem requires the homomorphism to be surjective.…”
Section: Introductionmentioning
confidence: 99%
“…So a homomorphism from G to H is surjective if every vertex of H is "used" by the homomorphism. There is still no complete characterisation of the complexity of determining whether there is a surjective homomorphism from an input graph G to a graph H, despite an impressive collection of results [1,17,18,19,27]. A homomorphism from V (G) to V (H) is a compaction if it uses every vertex of H and also every non-loop edge of H (so it is surjective both on V (H) and on the non-loop edges in E(H)).…”
Section: Introductionmentioning
confidence: 99%
“…We give their formal definitions in Section 2. Both problems are well-studied in the decision setting [2,22,23,21,34,42,44,46,47]. All three of the problems #SHom(H), #Comp(H) and #Ret(H) can be interpreted as problems requiring one to count homomorphisms with some kind of surjectivity constraint.…”
Section: Name: #Lhom(h)mentioning
confidence: 99%